2009
DOI: 10.1007/s11033-009-9692-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, expression and functional analysis of a putative RNA-dependent RNA polymerase gene from maize (Zea mays L.)

Abstract: RNA-dependent RNA polymerases (RdRPs) in plants have been reported to be involved in post-transcriptional gene silencing (PTGS) and antiviral defense. In this report, an RdRP gene from maize (ZmRdRP1) was obtained by rapid amplification of cDNA ends (RACE) and RT-PCR. The mRNA of ZmRdRP1 was composed of 3785 nucleotides, including a 167 nt 5' untranslated region (UTR), a 291 nt 3'UTR and a 3327 nt open reading frame (ORF), which encodes a putative protein of 1108 amino acids with an estimated molecular mass of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The expression of the key factors of RNA-silencing pathways usually is activated by virus infection at the transcriptional level to increase the activities of antiviral RNA silencing. For example, the expression of AGO1, AGO2, or RDR1 was usually induced by infection with diverse viruses (Yang et al, 2004;Alamillo et al, 2006;Zhang et al, 2006;Azevedo et al, 2010;He et al, 2010;Satoh et al, 2010;Várallyay et al, 2010;Du et al, 2011;Harvey et al, 2011). However, the molecular mechanisms of activation of the expression of these antiviral genes are unknown.…”
Section: Mir444-regulated Nitrate Signaling May Play Roles In the Ricmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the key factors of RNA-silencing pathways usually is activated by virus infection at the transcriptional level to increase the activities of antiviral RNA silencing. For example, the expression of AGO1, AGO2, or RDR1 was usually induced by infection with diverse viruses (Yang et al, 2004;Alamillo et al, 2006;Zhang et al, 2006;Azevedo et al, 2010;He et al, 2010;Satoh et al, 2010;Várallyay et al, 2010;Du et al, 2011;Harvey et al, 2011). However, the molecular mechanisms of activation of the expression of these antiviral genes are unknown.…”
Section: Mir444-regulated Nitrate Signaling May Play Roles In the Ricmentioning
confidence: 99%
“…RDR1 orthologs have been reported to be virus or salicylic acid inducible in different plants, including Arabidopsis, Nicotiana spp., Medicago truncatula, maize (Zea mays), and rice (Oryza sativa; Yang et al, 2004;Alamillo et al, 2006;He et al, 2010;Satoh et al, 2010;Du et al, 2011), and to provide basal resistance to several viruses by participating in the biogenesis of virusderived secondary siRNAs (Diaz-Pendon et al, 2007;Qi et al, 2009;Garcia-Ruiz et al, 2010;Wang et al, 2010). Recently, it was reported that RDR1 also is responsible for the production of a distinct class of virus-activated siRNAs, which direct widespread silencing of host genes to confer broad-spectrum antiviral activity in Arabidopsis (Cao et al, 2014), indicating that RDR1 plays a key role in antiviral resistance by silencing both the viral RNAs and the host immunity-related genes.…”
mentioning
confidence: 99%
“…Our previous studies showed that SCMV was the major causal agent of maize dwarf mosaic disease in China, and the Beijing isolate (SCMV-BJ) belonged to the prevalent strain [46]. It was reported that SCMV infection could elicit the accumulation of RDR1 mRNA, and silenced RDR1 maize plants were more susceptible to SCMV infection [47]. Co-expression assay demonstrated that the HC-Pro encoded by SCMV suppressed the RNA silencing induced by sense RNA and dsRNA, and down-regulated the accumulation of RDR6 mRNA [48].…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, RDR1, RDR2, and RDR6/SGS2/SDE1 have been highlighted as very important and crucial factors in antiviral plant defense responses in different plant species (Mourrain et al, 2000; Yu et al, 2003; Muangsan et al, 2004; Yang et al, 2004; Qu et al, 2005, 2008; Schwach et al, 2005; Adenot et al, 2006; Diaz-Pendon et al, 2007; Donaire et al, 2008; Garcia-Ruiz et al, 2010; He et al, 2010; Wang et al, 2010, 2011b). Although in certain cases, some RDRs mutants have no effects on the susceptibility to viruses carrying VSRs (Diaz-Pendon et al, 2007; Donaire et al, 2008).…”
Section: Antiviral and Antibacterial Roles Of The Small Rna Biogenesimentioning
confidence: 99%